Reconstruction of Maslow's Motivation Theory Through the Values of The Quran in Human Resources Management in The Era of Society 5.0 - Dhiyauz Zakiyyah; Kunti Mardiyatal Firdausi; Khilda Fitrotul Khabibah; Indah Aminatuz Zuhriyah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to reconstruct Maslow's motivation theory by integrating the values of the Qur'an in the context of human resource management (HR) in the era of Society 5.0. Maslow's theory, which has been the reference in understanding human work motivation, is considered to be secular and has not accommodated the spiritual dimension, especially in Muslim society. With a qualitative approach and the maudhu'i (thematic) interpretation method, this study traces the verses of the Qur'an that are relevant to Maslow's five hierarchies of needs: physiological, security, social, self-esteem, and self-actualization. The results of the study show that each level of need in Maslow's theory has a conceptual equivalent in the Qur'an, which enriches the dimensions of human motivation with divine values such as tazkiyah an-nafs, good deeds, and useful knowledge. This integration produces an